Global Antisemitism A Crisis of Modernity - Small, Charles Asher (Brill, 2020)
The essays are written by scholars from a wide array of disciplines, intellectual backgrounds, and perspectives, and address the conference's two inter-related areas of focus: global antisemitism and the crisis of modernity currently affecting the core elements of Western society and civilization. Rather than treating antisemitism merely as an historical phenomenon, the authors place it squarely in the contemporary context. As a result, this volume also provides important insights into the ideologies, processes, and developments that give rise to prejudice in the contemporary global context.